(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted during three consecutiveseasons viz 2003/04, 2004/05 and 2005/06, at Gezira Research StationFarm (latitude 14°24’N, longitude 33°31’E, and altitude 405 m asl) todetermine the optimum irrigation interval and nitrogen and phosphorusfertilization of barley (Hordium vulgare L.) for forage. Experimentaldesign was split-split plot design with three replications. Three irrigationintervals, viz every 10 days (W1), 15 days (W2) and 20 days (W3) wereassigned to the main plots, two phosphorus levels, (0P) and 96 kg P 2 O5 /ha (1P) were assigned to the subplots and three nitrogen levels (0N), 96(1N) and 192 kg urea/ ha (2N) were assigned to the sub subplots. Theexperiment was run during the 3 rd week of November, with a local varietyof barley (Baladi). Quantity of the applied water, dry matter yield at milkstage and of dry forage water productivity (kg dry matter / m 3 of appliedwater) were determined. The three years mean quantity of water appliedto the treatments W1, W2 and W3 were 4525, 4320 and 4290 m 3 / ha,respectively. The dry matter yields of barley in the three seasonsdecreased with increase of the irrigation interval. The comparativelyhigher dry matter yield in 2004/05 was attributed to lower day/ nighttemperatures during tillering - milk stage (30 - 75 days after sowing). Thethree years dry forage water productivities were 1.07 kg/m 3 (W1), 0.82kg/m 3 (W2) and 0.71 kg/m 3 (W3). The forage yield increased withincrease in level of N fertilization. The effect of P fertilization on drymatter yield was not significant. The highest dry matter yield wasassociated with the combination of irrigation every 10 days and 192 kgurea /ha.Key words: Barley; forage production; irrigation intervals, N and Pfertilization